2012
DOI: 10.1200/jco.2011.40.9433
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase II Study of Dacomitinib (PF-00299804), an Irreversible Pan–Human Epidermal Growth Factor Receptor Inhibitor, Versus Erlotinib in Patients With Advanced Non–Small-Cell Lung Cancer

Abstract: A B S T R A C T PurposeThis randomized, open-label trial compared dacomitinib (PF-00299804), an irreversible inhibitor of human epidermal growth factor receptors (EGFR)/HER1, HER2, and HER4, with erlotinib, a reversible EGFR inhibitor, in patients with advanced non-small-cell lung cancer (NSCLC). Patients and MethodsPatients with NSCLC, Eastern Cooperative Oncology Group performance status 0 to 2, no prior HER-directed therapy, and one/two prior chemotherapy regimens received dacomitinib 45 mg or erlotinib 150… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
149
0
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 236 publications
(157 citation statements)
references
References 22 publications
6
149
0
2
Order By: Relevance
“…Although chemotherapies, including cisplatin, carboplatin, gemcitabine, paclitaxel, docetaxel, and pemetrexed have shown activity in patients with EGFR mutations following failure of first-generation EGFR TKIs, these therapies have significant toxicity and patients invariably progress (30)(31)(32). So far, the second-generation inhibitors, including afatinib, neratinib, and dacomitinib, have provided limited therapeutic benefit in patients with drugresistant NSCLC (17,19,20). These compounds are hindered by dose-limiting toxicities associated with EGFR WT inhibition, and therefore, cannot be adequately dosed to inhibit the T790M drug-resistant mutation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although chemotherapies, including cisplatin, carboplatin, gemcitabine, paclitaxel, docetaxel, and pemetrexed have shown activity in patients with EGFR mutations following failure of first-generation EGFR TKIs, these therapies have significant toxicity and patients invariably progress (30)(31)(32). So far, the second-generation inhibitors, including afatinib, neratinib, and dacomitinib, have provided limited therapeutic benefit in patients with drugresistant NSCLC (17,19,20). These compounds are hindered by dose-limiting toxicities associated with EGFR WT inhibition, and therefore, cannot be adequately dosed to inhibit the T790M drug-resistant mutation.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a clinical trial afatinib failed to meet the primary end-point of overall survival in patients with NSCLC that had previously failed erlotinib and gefitinib (17). Both neratinib and dacomitinib also failed to offer overall survival benefits to EGFR mutant patients that have failed first-generation TKIs (18)(19)(20). Although these TKIs inhibit T790M, they are not mutant selective and seem to be more effective than erlotinib and gefitinib in inhibiting EGFR WT , and therefore, are hindered by dose-limiting toxicities (8,17,19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this compound displays improved pharmacokinetic properties, including increased bioavailability, half-life, and lower clearance as compared with the first-generation inhibitors (17). A phase II study comparing dacomitinib with erlotinib as a second-line treatment in unselected NSCLC patients gave positive results although a phase III in the same patient settings did not show any improvement (18). However, encouraging clinical activity has been demonstrated for dacomitinib as initial treatment in patients with advanced NSCLC carrying EGFR-activating mutations (19).…”
Section: Introductionmentioning
confidence: 99%
“…Patients in the IPASS study with EGFR mutations had a significantly prolonged PFS when treated with gefitinib (HR ¼ 0.48; 95% CI, 0.36-0.64, P < 0.001), whereas wildtype EGFR patients had inferior PFS with gefitinib (HR ¼ 2.85; 95% CI, 2.05-3.98, P < 0.001). Multiple studies have now compared EGFR TKIs to chemotherapy in the frontline therapy of patients with advanced or recurrent NSCLC with sensitizing EGFR mutations (46)(47)(48)(49). All of these studies showed a significant improvement in the primary endpoint of PFS with targeted therapy of EGFR mutation compared with systemic chemotherapy, with response rates with TKI ranging from 61% to 83% (Table 4).…”
Section: Individualized Therapymentioning
confidence: 97%